Pengembangan Multimedia Interaktif untuk Mendukung Proses Pembelajaran dengan Menggunakan Metode Multimedia Development Life: Pendahuluan, metode, hasil, kesimpulan - Ali Ikhwan auliana; Ummi Kalsum Siregar; Siddik Tambak; Sultan Haramain (GLOBAL SCIENTS PUBLISHER, 2026)
The rapid development of information and communication technology has brought significant changes to the field of education. One of the innovations widely adopted is interactive multimedia, which integrates text, images, audio, video, animation, and user interaction into a single learning medium. The development of interactive multimedia aims to enhance the quality of learning, increase students' learning motivation, and improve their understanding of the subject matter. This article employs a literature review method by analyzing various studies related to the development of interactive multimedia in education. The findings indicate that interactive multimedia can increase student engagement, accommodate different learning styles, and improve learning outcomes compared to conventional teaching methods. The development of interactive multimedia can be carried out using models such as ADDIE and the Multimedia Development Life Cycle (MDLC), both of which have proven effective in producing feasible and effective learning media.